The Cooperation of Plan International Indonesia and the Local Government of Sukabumi and West Lombok to Combat Child Marriage Through the Gema Cita Program - grisella, kezia andjanie; krishnamurti, indra v.a.; surawijaya, cecep indra (LIAISON JOURNAL OF BEST, 2024)
Child marriage remains a problem in Indonesia, despite the practice being banned in various international agreements and national regulations. Indonesia even ranks among the 10 counties with the highest prevalence of child marriage. As such, addressing this issue is important, particularly in fulfilling Indonesia’s commitment to the Sustainable Development Goals (SDGs). This thesis explores the cooperation between Plan Indonesia and the local government of Sukabumi and West Lombok through the Gema Cita program, which aims to combat child marriage. The study uses the theories of liberal institutionalism and international regimes to explore the strategies, challenges, and impact of this cooperation and how it fulfills the SDGs, particularly Target 5.3. The study used a qualitative case study approach and gathered primary and secondary data. The result shows that the SDGs, as an international regime, shape Indonesia’s national policies and local initiatives such as Gema Cita in addressing child marriage. Gema Cita’s strategy includes a comprehensive approach that effectively engages adolescents, schools, and communities to create sustainable effort against child marriage. The program’s strategy also aligns closely with Indonesia’s National Strategy on the Prevention of Child Marriage (STRANAS PPA). Despite facing various challenges, such as low awareness of child marriage and lack of support in the community, the program demonstrated effectiveness in raising awareness, support, and influencing policy changes in the areas. The roles and responsibilities of Plan Indonesia and the local government contribute to the program’s success. Plan Indonesia’s focus on capacity building, advocacy, and evaluating complements the local government’s role in formalizing agreements, enforcing policies, and coordinating efforts. The findings suggest that such cooperation is important for child marriage prevention program like Gema Cita. Keywords: Gema Cita, Plan Indonesia, child marriage, local government cooperation, sustainable development goals (SDGs)